Civic welfare : training service, volume II - Padilla, Reynaldo A. (Manila, 2006)
The basic outline of this book will follow most of the topics contained in the syllabus prepared and approved by the officers and members of the Association of CWTS implementors of the Philippines, Inc. on April 30, 2003. It is my hope that this current book , forming the second part of civic welfare service, would complete the said syllabus
Keywords: Civic welfare- study and teaching; NSTP- study and teaching